Identity Politics in The Scales of Fiqh Siyasah: an Analysis of The Concepts of Walayah and Kafa'ah in Public Leadership - Zulfaidah, Rena; Kholik, Muhamad Abdul; Rajak, Rahmat (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2026)
Religious identity politics has become a controversial phenomenon in the political landscape of pluralistic countries, including Indonesia, often triggering polarization and testing the principles of democratic inclusivity. This study aims to analyze this phenomenon through the framework of Fiqh Siyasah (Islamic Constitutional Law), focusing on the dialectic between two main requirements of leadership Walāyah (authority/religious identity) and Kafā'ah (competence/managerial eligibility). Using a qualitative normative-philosophical literature study method, primary data in the form of the Qur'an and Hadith, as well as secondary data from classical and contemporary Fiqh Siyasah literature, were analyzed using the Usūl al-Fiqh and Maqāshid Syariah approaches. The results of the study show that Fiqh Siyasah demands the perfect integration of these two concepts. Shariah arguments establish Walāyah as a moral-theological commitment, but explicitly juxtapose it with Kafā'ah, which includes expertise, honesty, and managerial capacity as essential requirements for effective leadership (e.g., QS. Al-Qashash: 26). The tendency of modern identity politics is to absolutize formal Walāyah, thereby neglecting Kafā'ah. The Sharia implication of neglecting Kafā'ah is the emergence of collective damage (mafsadah) that threatens Maslahah 'Āmmah (public interest), including the destruction of unity (wahdah) and the emergence of incompetent leadership that fails to uphold universal justice ('Adalah). The conclusion of this study confirms that identity politics is only valid and constructive if it is directed at electing leaders with integrity and proven competence, making Kafā'ah a crucial consideration in Sharia law in order to realize the goal of Rahmatan lil 'Ālamīn.